Patient‐reported outcomes and joint status across subgroups of US adults with hemophilia with varying characteristics: Results from the Pain, Functional Impairment, and Quality of Life (P‐FiQ) study. (2nd March 2018) - Batt, Katharine; Boggio, Lisa; Neff, Anne; Buckner, Tyler W.; Wang, Michael; Quon, Doris; Witkop, Michelle; Recht, Michael; Kessler, Craig; Iyer, Neeraj N.; Cooper, David L.
Abstract: Introduction: Pain and functional impairment associated with joint disease are major problems for people with hemophilia, and impact on health‐related quality of life (HRQoL) may vary across groups defined by demographic and treatment‐related characteristics. Objective: To evaluate differences in overall HRQoL, pain, function, and joint status between P‐FiQ study subgroups. Methods: Adult males with hemophilia and a history of joint pain/bleeding completed a pain history and the patient‐reported outcome instruments EQ‐5D‐5L, Brief Pain Inventory v2 Short Form (BPI), International Physical Activity Questionnaire (IPAQ), and Hemophilia Activities List (HAL); optionally, joint status was assessed (Hemophilia Joint Health Score v2.1 [HJHS]). Scores were analyzed between subgroups across sets of participant characteristics. Results: A total of 381 adult males with hemophilia were enrolled, with median age of 34 years. Worse scores on EQ‐5D‐5L index, BPI pain severity/interference, HAL overall score, and HJHS were generally associated with being college educated, unemployment, self‐reporting both acute and chronic pain, and self‐reporting anxiety/depression. Conclusions: Measures of joint status and HRQoL were consistently lower in participants who had higher educational levels, were unemployed, self‐reported having both acute and chronic pain, and self‐reported having anxiety/depression. A greater understanding of the association of these factors with disease outcomes may improve individualized patient management.